Internal Migration and Inclusive Economic Growth in Sumatra: An Islamic Economics Perspective - Yosy Arisandy; Shahrul Nizam Bin Salahuddin; Yosza Bin Dasril; Fuad Mahfudz; Tri Chamauliddah (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2026)
Purpose: Persistent regional inequality in Indonesia, particularly across Sumatra Island, continues to constrain inclusive economic growth and upward social mobility. This study investigates how internal migration functions as a pathway for socioeconomic advancement and reinterprets this process through Islamic economic principles of justice (al-‘adl) and equitable welfare within the framework of maqāṣid al-sharī‘ah.Design/Methodology: This study employs a qualitative approach based on in-depth interviews with 10 purposively selected migrants, supported by relevant literature and official migration statistics. Data were analyzed by identifying recurring patterns in migrant narratives and conducting an interpretive analysis of Islamic ethical-economic sources. Analytical rigor was ensured through source and theoretical triangulation, systematically comparing interview findings wiakth established migration theories and official statistical data.Findings: The study finds that internal migration is experienced as a form of “economic hijrah,” reflecting processes of human capital transformation and improved livelihoods. Domestic remittances emerge as a key mechanism for redistributing economic resources, while migration contributes to the gradual shift toward merit-based social mobility consistent with Islamic egalitarian values.Practical Implications: These findings highlight the importance of inclusive migration policies and underscore the strategic role of Islamic financial institutions in optimizing domestic remittance flows to support sustainable regional development.Originality/Value: This study contributes to the literature by offering an integrated analytical perspective that bridges migration theory and Islamic economics, introducing the concept of “economic hijrah” as a novel framework for understanding migration as both an economic strategy and an ethically grounded process of achieving human dignity